PERKAWINAN DIBAWAH UMUR (Studi Pada Masyarakat Bajo Kecamatan Soropia Kabupaten Konawe) - Hasniran Hasniran (IAI Al-Mawaddah Warrahmah Kolaka, 2019)
Abstract Underage marriages in the Bajo community, Soropia Subdistrict, Konawe Regency, show that the factors causing underage marriages in the Bajo community are Educational Factors, Economic Factors, Hereditary Factors, Religious Understanding Factors, Technology Factors, Environmental Factors.